Affective factors in second language writing ability attrition among English as foreign language learners - Asgari, Azadeh (2012)
The prominent intention of this study is to investigate the influence of affective factors on second language (L2) writing ability attrition among English foreign language learners. The research objectives were investigated to identify a) the differences between learners’ writing performance at the two stages, b) the effect of proficiency levels and groups of learners on L2 writing attrition, c) the relationship among affective factors and second language writing ability attrition, and d) the determinant predictor factors on L2 writing ability attrition among Persian language learners. The intended research design methodology for this dissertation was as a mixed method design starting with a quantitative method followed by a qualitative method. In the quantitative phases, after making an initial pilot study, a TOEFL writing test, the General Background Question (GBQ) survey, and the Attitude/Motivation Test Battery (AMTB) questionnaire were conducted among 366 learners who were randomly assigned among the EFL learners at the Kish English Institute’s (KEI) at the two stages. The dependent variables are the comparison of scores in the learners’ TOEFL writing performance based on the five aspects of Jacobs’ rubric including the overall score of the essay and the score of each component between two groups across the three levels of language proficiency. The Statistical Package for Social Science software version 16 was used to assist in coding the raw quantitative data. After the analysis of quantitative phase was done, the structured interview was conducted among 12 volunteers at the Kish English Institute’s (KEI) and recorded with their permission to explore the in-depth perception of the EFL learners regarding the L2 writing experience. The outcomes from the qualitative data were used to determine common responses to compare perceived issues and recommendations in language attrition and other learning factors. Consequently, the quantitative data analysis consistently illustrated statistically significant L2 writing aspects (content, organization, vocabulary, language use, and mechanics) along with their performance in the two various stages within a period of six months interval. Likewise, the null hypothesis regarding the impact of proficiency levels and groups of respondents was rejected for four aspects of L2 writing and this hypothesis was not supported by the mechanics factors. The length of L2 exposure was also significantly affective in the advanced level of the EFL learners. The other affective factors also have high associations in predicting L2 writing attrition. The qualitative interview data in the following phase was consistent with the detected quantitative results in the first phases:participants admitted that lack of specific knowledge, specific vocabulary for an unfamiliar topic, lack of confidence in speaking, age, educational level, lack of motivation and negative attitude toward learning and speaking can be major factors leading to the attrition. Moreover, they also emphasized the effect of anxiety in the English classes. The results of this study will enlighten educators, administrators and support staff of the barriers to complete the ESL/EFL program and to propose solutions that will help learners to succeed. Finally, some pedagogical implications that would prevent the L2 writing attrition were presented.